COMMUNICATIVE AND PRAGMATIC FEATURES OF MODALITY IN THE UZBEK LANGUAGE - Gulasal Fayzullo qizi Khayrullayeva (International Journal of Literature and Language Studies, 2026)
This article analyzes the communicative and pragmatic features of modality in the Uzbek language. The study examines the role of the category of modality in speech communication and its significance in expressing the speaker’s attitude toward reality, information, and the interlocutor. Particular attention is paid to the manifestation of modality through various linguistic units, its functions in achieving communicative goals, and its role in constructing pragmatic meaning. The article also reveals the specific features of modal expressions in relation to speech situations, context, and communicative intentions. The findings contribute to a deeper understanding of the semantic, communicative, and pragmatic aspects of modality in the Uzbek language.